Rekomendasi Pemupukan Kalium untuk Tanaman Nenas Berdasarkan Status Hara Tanah - La Ode Safuan; Roedhy Poerwanto; Anas Dinurrohman Susila; , Sobir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Potassium (K) is required in a large amount for plant growth and production of most fruit crops, including pineapple. However, excess application may decrease its growth and production. Therefore, fertilizer application must be site specifi c, based on soil nutrient status and plant requirements. The aims of the research were (1) to determine the soil K nutritional status of pineapple and (2) to determine the optimum dosage of K fertilization for pineapple grown in Sawah Baru, Darmaga, Bogor. The research was conducted using split plot randomized block design with fi ve soil K status as main plots i.e. 0, 70, 140, 210, and 280 kg K2O ha-1 representing status levels of very low, low, moderate, high, and very high, respectively. The sub plot was dosage of K fertilizer i.e. 0, 200, 400, 600, and 800 kg K2O ha-1. The result of the research showed that plant growth and production of pineapple were improved by soil K nutrient status and dosage of K application. The level of soil K nutrient availability was classifi ed into low (<14 ppm K2O), medium (14-50 ppm K2O), and high (>50 ppm K2O). Potassium fertilizer is recommended for the soil with low soil K status of 634 kg K2O ha-1 .